Energy and exergy analysis of a cylindrical hot water storage tank: experimental and CFD analysis - Kropas, Tomas; Streckienė, Giedrė (International Conference “Environmental Engineering”, 2020)
Active solar water heating systems typically include hot water storage tanks. The selection of the storage system strongly affects the performance of the entire system. This article presents a detailed analysis of a hot water storage tank during charging and dynamic charging-discharging mode. A numerical model using computational fluid dynamics for the storage tank was developed to investigate the temperature distribution inside of it. Transient thermal analysis was carried using ANSYS Fluent. The numerical model was validated with the experimental results. The energy and exergy analysis as an important tool for the evaluation of the thermal systems quantitatively and qualitatively was performed. The calculation procedures were described. The energy and exergy efficiencies, heat losses were calculated for steady and dynamic processes. Effect of mass flow rate was analysed. The results from parametric analysis showed that charging dynamics reduced the thermocline and efficiency of the hot water storage tank. The dependency of the exergy efficiency of the heat storage tank on the reference environment temperature during the dynamic operation was analysed. Exergy efficiencies for two cities with different climates were compared. This indicated that the higher environmental temperature gave lower exergy efficiency of the storage tank.
Keywords: heat storage tank; energy efficiency; exergy efficiency; computational fluid dynamics (CFD); fluid flow; environmental temperature; climate